A norms mining approach to norms detection in multi-agent systems - A. Mahmoud, Moamin; Ahmad, Mohd Sharifuddin; Ahmad, Azhana; Mohd Yusoff , Mohd Zaliman; Mustapha, Aida (IEEE, 2012)
In this paper, we propose a norms mining technique for a visitor agent to detect the norms of a community of local agents to comply with the community's normative protocol. In this technique, the visitor agent is equipped with an algorithm, which detects the potential norms through the system's log file, interactions with the local agents, and observing the local agents in action. The visitor agent detects the norms from these sources depending on their availability. Due to security issues, access is prevented to one or more of these sources. The norms mining technique entails the process of data formatting and filtering and identifying the norms' components that contribute to the strength of the norms. The results of an example mining operation show that the technique is successful in discovering the potential norms.